Efficient catalytic degradation of methylene blue by a novel Fe3+-TiO2@CGS three-dimensional photoelectric system - Li, Jian; Wang, Yufei; Guo, Fanhui; Chen, Juan; Wang, Jinxi; Fan, Xiaoyong; Li, Baoning; Verma, Santosh Kumar; Wei, Qingbo; Yan, Long; Wu, Jianjun (Frontiers in Chemistry, 2022)
A novel three-dimensional photoelectric system was designed and constructed for the degradation of methylene blue (MB) via the photocatalysis, electrocatalysis, and photoelectrical catalysis. In this study, an electrode consisting of Ti/RuO2-IrO2-SnO2-CeO2 prepared via a thermal oxidation coating method as a dimensionally-stable anode (DSA), a titanium sheet as cathode, and Fe3+-doped TiO2 loaded on coal gasification slag (CGS) (Fe3+-TiO2@CGS) as photocatalyst. The factors affecting the efficiency of supporting electrolyte, current density, and initial pH were systematically investigated in this photoelectrical system. Importantly, the results revealing that the Fe3+-TiO2@CGS three-dimensional photoelectric system could exhibit efficient synergistic performance of photocatalysis and electrocatalysis with a synergistic factor of 1.11. Additional, the photo-generated holes(h+) were generated by light irradiation as well as the direct anodic oxidation. The hydroxyl radicals (HO·) radicals were generated via other pathways. These active species showed highly-oxidizing ability, which is beneficial to the degradation of MB. As a representative, the system showed super high degradation efficiency at the pH of 11 and the current density of 18.76 mA·cm-2, and with NaCl as supporting electrolyte, the degradation yield can reach 99.98% after a photoelectrical treatment of 60 min. We believed that the present novel Fe3+-TiO2@CGS three-dimensional photoelectrical system would provide a guidance for highly efficient catalytic degradation of organic contaminants.